Widespread sea surface salinification induced by tropical cyclones over the Changjiang River Plume - Shoude Guan; Mengya Huang; I-I Lin; Hui Wu; Yaoting Lin; Ziyi Wu; Yihan Zhang; Fei-Fei Jin; Weili Wang; Xin Hong; Cheng Li; Zhenmin Liu; et al. (Communications Earth & Environment)
Abstract Riverine plumes greatly shape ocean environments and ecosystems. The Changjiang River plume, widely spreading in the Yellow and East China Seas in summer, induces extremely low surface salinity and threatens local aquaculture and fisheries. Passage of tropical cyclones potentially increases surface salinity by stirring upper oceans, yet the extent of cyclones’ effects on the Changjiang River Plume extension and its mechanisms remains less explored. Here, combining satellite and in-situ observations with numerical experiments, we reveal a widespread surface salinification induced by Lekima (2019), with the maximum salinification reaching 6.5 psu and an 83% Changjiang River Plume contraction. Tropical cyclone-induced vertical mixing contributes to this dramatic salinification, while horizontal advection can either contribute to or offset the salinification, depending on specific locations. Further examination of surface salinity during 2015–2022 suggests that tropical cyclones can effectively restrict the Changjiang River Plume extension, potentially shielding fishing and aquaculture industries from low-salinity-related disasters.